THE STRATEGY PROGRAM FOR IMPROVING AVIATION VOCATIONAL COLLEGE STUDIES THROUGH INTERNATIONAL TRAINING INTEGRATION - Wirawan, Yani Yudha (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
Merdeka Belajar Kampus Merdeka (MBKM) Program aims to improve graduates' abilities, soft skills, and hard skills following the needs of the times to prepare graduates to become superior and personable future leaders and the acceleration of Indonesian human resources education is more focused on vocational education human resources. This research aims to develop appropriate strategies to improve human resources competency to support the transformation of the transportation sector by integrating the international training curriculum into the curriculum and syllabus of higher education study programs so that it has an impact on increasing the quality of the leading performance indicators in the independent learning campus of independent higher education. This research uses the Strengths, Opportunities, Aspirations, and Results (SOAR) analysis method to analyze the internal factors' Strengths, Aspirations, and external factors' opportunities and results, which are the basis for determining strategy. The results of the research analysis conducted on the strategy for improving study programs in the higher education environment of the Ministry of Transportation aviation vocational college through the integration of international training is a new policy that is the output of the international curriculum and syllabus of higher education, international competency certificates to benefit from improving the quality of education and its relevance to the needs of the global market—the implementation impact to improve competency in supporting the transformation of the transportation sector.